Experience of nurses in Caring for patients with COVID-19: A descriptive qualitative study - Asha P. Shetty; Shree Mishra; Rakesh V. Radhakrishnan; Mahalingam Venkatesan; Vishnu Renjith (Elsevier, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) had a significant impact on nursing practice. Managing a wide range of patients, with those ranging from mild infection to those with critical illness requiring mechanical ventilation, posed unprecedent challenges to nurses. Method: The aim of the study was to explore and describe the experiences of nurses in caring for patients with COVID-19. We adopted a qualitative descriptive design to study the experiences of nurses regarding the management of patients with COVID-19. The study was conducted among ten nurses who were involved in the care of COVID-19 patients at a tertiary care teaching hospital in south-east India. The data were analyzed using the Braun and Clarke thematic analysis method. Results: The study participants consisted of 8 female and 2 male nurses and were in the age group of 22-31 years. Five major themes emerged during data analysis. The themes were 1. personal problems, 2. challenges in the work environment, 3. professional preparedness, 4. support systems and 5. satisfaction with patient care. Conclusion: The COVID-19 pandemic has had a significant impact on the lives of nurses. Nurses faced a plethora of problems and challenges while taking care of people with COVID-19. Nurses experienced personal problems, including fear of contracting illness and social stigma. There were various challenges in the work environment, such as difficulties in using personal protective equipment. The other major themes were professional preparedness, support systems and satisfaction with patient care. It is essential to acknowledge that continuous training is essential and that adequate provision of facilities can enhance the morale of nurses, resulting in better job satisfaction.